The Effect of Firm Growth, Firm Size, and Asset Structure on the Debt Policy - Hasirah Hasirah; Muhammad Ali; Andi Aswan (Magister Management, Hasanuddin University, 2021)
This study aims to examine and analyze the effect of company growth, company size, and asset structure on the debt policy of State-Owned Enterprises in Indonesia. Data collection was carried out by using descriptive quantitative methods, using secondary data instruments on the annual financial statements of state-owned companies listed in the Indonesia Stock Exchange for the period of the year 2013-2019. The research sample used the purposive sampling method with certain criteria from 133 companies and resulted in 17 companies with 112 data samples. The data were analyzed using multiple regression analysis with the help of the SPSS AMOS version 2.0 application. The results showed that company growth had a positive and significant effect on debt policy. Furthermore, the results show that company size has a positive and significant effect on debt policy. The analysis also shows that the asset structure indicates a positive and significant relationship to debt policy